Factors associated with suicidal ideation among medical residents in Tehran during the COVID-19 pandemic: A multicentric cross-sectional survey. - Fahimeh Saeed; Elaheh Ghalehnovi; Mahdieh Saeidi; Neda Ali Beigi; Mohsen Vahedi; Mohammadreza Shalbafan; Leila Kamalzadeh; Ali Nazeri Astaneh; Amir Hossein Jalali Nadoushan; Sheikh Shoib (PLoS ONE, 2024)
Background The mental health of medical residents, challenged by their intensive training, is of utmost concern. In light of reported suicides among Iranian medical residents in 2021, this study investigates the factors behind suicidal ideation among medical residents during the COVID-19 pandemic in Tehran. Methods This study conducted a cross-sectional online survey among medical residents in various specialties in Tehran, Iran, amidst the COVID-19 pandemic. Suicidal ideation was assessed using the Beck Scale for Suicidal Ideation (BSSI), while depression, anxiety, and stress were measured using the DASS-21. It also collected demographic and clinical data from the participants. The data were analyzed using descriptive statistics, the Chi-square test, and multiple linear regression to examine the prevalence and determinants of suicidal ideation among medical residents. Results The study enrolled 353 medical residents and found that 34.3% of them had suicidal ideation, with 10.2% indicating a high risk. The study also found high levels of depression, anxiety, and stress among the participants. The variables that significantly predicted suicidal ideation were depression, history of alcohol/substance use, personal history of suicide attempts, history of self-mutilation, family history of suicide attempts, number of shifts in a month, death of close persons because of COVID-19, and income. Depression was the strongest predictor of suicidal ideation. Conclusion These findings underscore the urgent need for effective interventions and support systems to address the mental health needs of medical residents in Iran. The strategies should prioritize destigmatizing mental health, promoting access to mental health services, fostering a supportive training environment, and enhancing income opportunities.